SIMULTANEOUS EFFECTS OF WORK STRESS AND CYBERLOAFING ON EDUCATIONAL STAFF PERFORMANCE IN A INDONESIAN PUBLIC UNIVERSITY: A QUANTITATIVE EX POST FACTO ANALYSIS - Tyas Wulaningrum; Shely Cathrin; Zafrullah Zafrullah; Kurnia Novianti (Universitas HKBP Nommensen, 2026)
Job stress is a major psychological challenge for educational staff in higher education institutions (HEIs), often triggered by high administrative workloads and time pressure. This study analyzes the association between job stress, cyberloafing, and the performance of 223 educational staff at Universitas Negeri Yogyakarta (UNY). Using a quantitative approach with an ex-post facto design, data were collected through structured questionnaires (Aiken’s V: 0.67–1.00; Cronbach’s Alpha > 0.87) and analyzed using multiple linear regression. The findings reveal that job stress is positively associated with performance (t = 7.479; p < 0.05), and cyberloafing also shows a significant positive correlation (t = 3.630; p < 0.05). Simultaneously, both variables explain 43.5% of the variation in performance (F = 84.771; R2 = 0.435). These results suggest that within the specific context of Indonesian HEIs, moderate stress and brief digital recovery are linked to higher productivity. Practically, this study recommends that university administrators implement adaptive HR policies, such as workload management and educational digital literacy programs, rather than strictly restrictive internet policies, to support sustainable staff performance.